The effect of emotional intelligence levels of intensive care and clinical nurses on psychological resilience - Gümüş, Cemile; Tülay Yılmaz Bingöl; Nermin Gürhan (KHD-Production, 2025)
Nurses must have communication skills, empathy, and the ability to deal with the challenges of patient care effectively. Emotional intelligence and psychological resilience are skills that nurses can develop in adapting, collaborating, and providing quality patient care. This study aims to determine the effect of the emotional intelligence levels of intensive care and clinical nurses on their psychological resilience levels. In this descriptive cross-sectional study, 252 intensive care and ward nurses met the study sample.